Effects of Corporate Social Responsibility Dimensions on Customer Based Corporate Reputation in the Nigerian Insurance Industry - Yusuf, Nafisa Aminu; Mustaffa, Che Su; Mohamad, Bahtiar (2018)
The objective of this paper is to examine empirically the influence of corporate social responsibility on customer-based corporate reputation of the Nigerian insurance industry. The data for this study was collected from 327 customers of insurance companies in Nigeria. The study utilized PLS-SEM path modeling with the aid of Smart PLS 2.0 software to test the research hypotheses. The findings revealed that two CSR dimensions (Economic concern and social equity) have significant positive effects on the CBCR in the Nigerian insurance industry. However, the study failed to support the second hypotheses that predicted the positive relationship between environmental concern and CBCR. The study recommended the need for insurance companies to engage in aggressive CSR activities with a view to enhance awareness and increase their level of penetration within the teaming Nigerian populace that are yet to appreciate the benefits of insurance services in the country.